ANALISIS KESULITAN BELAJAR SISWA SLOW LEARNER KELAS III SDN SOCAH 2 BANGKALAN - Dwi Maulidia Suciati; Dewi Febriyanti; Fanni Aulia Ardhani; Muhammad Shubhi Alwahidi; Nafiatul Adawiyah; Nova Estu Harsiwi (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT The presence of slow learner students in regular classrooms presents unique challenges, as their learning needs are often not fully accommodated by existing instructional practices. This condition may affect not only their participation in classroom activities but also the development of their academic and psychological competencies. This study was conducted to provide a comprehensive description of the learning difficulties experienced by third-grade slow learner students at SDN Socah 2 Bangkalan within the context of inclusive education. A descriptive qualitative approach was employed, utilizing observation, interviews, and documentation as the primary data collection techniques. Data were analyzed through the processes of data reduction, data display, and conclusion drawing, supported by source and technique triangulation. The findings revealed that among the 21 students observed, 6 students (28.6%) were categorized as low, 11 students (52.4%) as moderate, and 4 students (19.0%) as high. Further findings indicated difficulties in literacy and numeracy skills, a slower pace in understanding learning materials, limited ability to maintain concentration, and suboptimal self-confidence during the learning process. These findings suggest that the learning experiences of slow learner students are shaped by the interaction between academic and psychological factors. Therefore, the implementation of inclusive education requires more adaptive instructional practices, continuous support, and active collaboration among teachers, schools, and parents to effectively address students' diverse learning needs. ABSTRAK Keberadaan siswa slow learner dalam kelas reguler menghadirkan tantangan tersendiri karena kebutuhan belajar mereka sering kali tidak sepenuhnya terakomodasi oleh pola pembelajaran yang berlaku. Kondisi tersebut dapat berdampak pada keterlibatan siswa dalam proses belajar sekaligus memengaruhi perkembangan kemampuan akademik dan psikologisnya. Kajian ini dilakukan untuk memperoleh gambaran mengenai kesulitan belajar yang dialami siswa slow learner kelas III di SDN Socah 2 Bangkalan dalam konteks pendidikan inklusif. Penelitian menggunakan pendekatan kualitatif deskriptif dengan memanfaatkan observasi, wawancara, dan dokumentasi sebagai sumber data utama. Analisis dilakukan melalui proses reduksi data, penyajian data, dan penarikan kesimpulan yang diperkuat dengan triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa dari 21 siswa yang diamati terdapat 6 siswa (28,6%) pada kategori rendah, 11 siswa (52,4%) pada kategori sedang, dan 4 siswa (19,0%) pada kategori tinggi. Temuan lebih lanjut memperlihatkan adanya kesulitan dalam literasi dan numerasi, kebutuhan waktu belajar yang lebih panjang, keterbatasan dalam mempertahankan konsentrasi, serta kepercayaan diri yang belum berkembang secara optimal. Keseluruhan temuan tersebut menunjukkan bahwa pengalaman belajar siswa slow learner dibentuk oleh keterkaitan antara aspek akademik dan psikologis, sehingga penyelenggaraan pendidikan inklusif memerlukan pembelajaran yang lebih adaptif, pendampingan yang berkesinambungan, serta kolaborasi aktif antara guru, sekolah, dan orang tua.